The Surabaya City Government’s Creativity in Making Surabaya a Healthy City - Mangihut Siregar (Public Service and Governance Journal, 2025)
The city of Surabaya is known by various names such as the City of Heroes, Industrial City, and Harbour City. Recently, it has also been recognized as a Healthy City. This status was achieved through efforts at both local and global levels. This study explores the elements that contribute to Surabaya's recognition as a healthy city. Utilizing a qualitative research approach, the study involved subjects from the Surabaya City Government, community leaders, and selected residents. Data was gathered through methods including observation, interviews, literature reviews, and document analysis. The findings indicate that Surabaya's success as a healthy city is supported by multiple factors: substantial land assets, an adequate regional budget (APBD), a sufficient number of hospitals, effective empowerment of street vendors (PKL), and the establishment of Kader Surabaya Hebat (KSH). The Surabaya City Government has effectively leveraged the region's potential to achieve these results.